Análise de deformações específicas de tração na fibra inferior de revestimento asfáltico através de instrumentação e métodos numéricos - Carvalho, Nielson Tôrres Neves de (2017)
The use of numerical methods to estimate stress, strains and displacements in road pavements is commonly used in the design stage to predict pavement performance. This estimate may lead to inaccuracies which reflect over or undersizing, economic losses and early loss of pavement service. It is of great importance to measure these differences by comparing the estimates of numerical methods commonly used and the direct measurements on the pavement. One method of directly measuring mechanical behavior of the pavement is to use the instrumentation, which can be adopted to measure stress, strains and displacements, as well as environmental factors such as temperature. Among the most critical parameters is the horizontal tensile strain in the lower fiber of the asphalt binder or hydraulic binder cemented layers, which is directly linked to the fatigue process and, consequently, to the cracking of these layers. In this work was carried out the evaluation of the specific horizontal strains measured by an H-Gage type sensor installed at the lower fiber of the asphaltic layer in the experimental road of the Federal University of Sergipe. These field results were compared with the numerical estimates through method of multiple elastic layers with the use of software AEMC/SisPAV (FRANCO, 2007) and finite element method with the use of software ANSYS ®, aiming to evaluate the accuracy of numerical estimates. Some field measurements were rejected because of problems arising from sensor installations, but the results of the validated measurements presented coherent behavior. In the comparison of the results of the numerical modeling with the field measurements, the finite layer method showed higher values than the instrumentation, while the finite element modeling presented lower values. By evaluating the fatigue prediction, the numerical estimates revealed fatigue life very different to field measurements, being smaller in the multiple layer method and relatively bigger in the finite element method.